Potential of soybean-velvet bean combination tempe in improving cognitive function - Astawan, Made; Damayanti, Aprilia F.; Wresdiyati, Tutik; Afifah, Diana N.; Rahmawati, Irma S. (Narra Sains Indonesia, 2024)
Velvet bean is a native Indonesian legume containing L-dopa, yet it remains underutilized. The aim of this study was to analyze the effects of different types of tempe (soybean, velvet bean, and their combination) on cognitive function, brain histology, dopamine levels, and serum β-amyloid in rats, as well as to identify the parameters most influencing cognitive function, including brain mass and volume, hippocampal neuron count, and dopamine and β-amyloid levels. An experimental study was conducted using a completely randomized design with one factor: the protein source of diet. Five rat groups were included based on protein sources: non-protein, casein control, soybean tempe flour, velvet bean tempe flour, and a combination of soybean and velvet bean tempe flour. This study examined cognitive performance by measuring maze completion time, while brain mass and volume, hippocampus histology for neuron cell counts in the dentate gyrus section, cornu ammonis 1 (CA1), and cornu ammonis 3 (CA3), brain dopamine and β-amyloid serum levels were measured after eight weeks of intervention. Our data indicated that rats deprived of protein had significantly slower maze completion times (p<0.001), underscoring the importance of protein in cognitive processes. Rats treated with non-protein rations had significantly lighter brain masses (p<0.001) than other treatments. Histological analysis of the hippocampus showed that the three types of tempe rations helped maintain the number and density of neuron cells in the dentate gyrus and CA3 of the hippocampus. Additionally, the protein in the ration could increase dopamine levels and suppress serum β-amyloid levels. There was a strong correlation between brain volume and neuron cell density in the dentate gyrus section of the hippocampus with cognitive function. These results highlight the promising role of combination tempe in increasing cognitive function, brain mass and volume, dopamine levels, and suppressing serum β-amyloid.